La représentation des élites grecques - Irini Apostolou (Cahiers Balkaniques)
In the Greek area, despite the realization of portraits of Phanariots and dignitaries, the art of portraiture remained marginal till the creation of the new Greek State and during its first decades. Indeed the lack of a structured bourgeoisie and of arts institutions was a source of a limited production of portraits. In the present paper, we want to study the production and evolution of the sets of painted and photographic portraits of the Greek elites through some precise examples in parallel with French works, obeying a long pictorial tradition since the Renaissance.